Does Intensive Training of Attention Influence Cognitive Fatigability in Patients With Acquired Brain Injury? - Holmqvist, Anna; Bartfai, Aniko; Markovic, Gabriela; Möller, Marika C. (Frontiers in Neuroscience, 2021)
Research Objectives: Impairments in attention and the speed of information processing are central to the experience of cognitive fatigue in patients with acquired brain injury (ABI). Attention may be improved through intensive training in a rehabilitation setting. The aim of the study was to investigate the feasibility of reducing CF using attention training and to explore the effect of two different approaches to attention training. Design: Randomised controlled study in a rehabilitation setting. Participants: 59 patients (age 19-59 years) with mild to moderate stroke or traumatic brain injury in the early (<4 month) phase. Interventions: Patients were randomly assigned to intensive specific training with Attention Process Training (APT) or Activity-Based Attention Training (ABAT) for 3-5 days per week for a period of 5-6 weeks with a total of 20 hours, in addition to traditional interdisciplinary rehabilitation. Main Outcome Measure: CF was conceptualised as performance decline in terms of an increased number of incorrect responses between the first and the last quintiles of the Paced Auditory Serial Addition Test (PASAT). A negative result was defined as fatigability. The evaluator of fatigability was blinded to treatment. Results: At baseline, there were no differences between the groups in age, education, reasoning, anxiety or depression. After training, a significant treatment effect was found (p=.020), as the APT-group, but not the ABAT-group, had improved. However, after controlling for baseline differences regarding CF on the PASAT-f, the difference was no longer significant. Conclusions: The results indicate that cognitive training might be a feasible method for reducing CF through attention training and that patients with high levels of CF benefit most from attention training. The type of intervention provided, whether specific or activity-based attention training, appears to be of less importance, as there was no treatment effect after controlling for the baseline level of CF. Future studies are required to confirm the validity of the findings.